Reformas legales al art. 843 del Código Civil relacionado a la cuantía para la constitución del patrimonio familiar - Poveda Vega, Sergio Vinicio (2015)
The Constitution of the Republic of Ecuador protects the rights of the person, property, family life, providing a legal tool for this purpose, making this protection a progressive extension of this Constitutional right, to material goods family, the family. The Civil Code refers to the credit of the couple. Both spouses may establish equity on property owned by either spouse, for your children. You can also do this person a widow, divorced or single. In these circumstances the Civil Code Article 843 states that the amount of goods that integrate family assets may not exceed forty-eight thousand dollars, with an additional four thousand dollars each child; we face a different reality, if we consider that the country's situation is different, since a normal home for a small family, with three bedrooms its value ranges from 60 to 80,000 dollars, so the average family can not constitute their property in limiting homestead established by the aforementioned statute. In this situation, it should reform the Civil Code as to the amount of the Homestead